Land development and road salt usage drive long-term changes in major-ion chemistry of streamwater in six exurban and suburban watersheds, southeastern Pennsylvania, 1999–2019 - Rossi, Marissa L.; Kremer, Peleg; Cravotta, Charles A.; Seng, Krista E.; Goldsmith, Steven T. (Frontiers in Environmental Science, 2023)
In urbanized areas, the “freshwater salinization syndrome” (FSS), which pertains to long-term increases in concentrations of major ions and metals in fresh surface waters, has been attributed to road-salt application. In addition to FSS, the water composition changes as an influx of sodium (Na+) in recharge may displace calcium (Ca2+), magnesium (Mg2+), potassium (K+), and trace metals by reverse cation exchange. These changing ion fluxes can result in adverse impacts to groundwater and surface waters used for municipal supplies. Few datasets exist to quantify the FSS on a watershed scale or link its manifestation to potential controlling factors such as changes in urban development, land use/land cover (LULC), or wastewater treatment plant (WWTP) discharges in upstream areas. Here, we use two decades (1999-2019) of monthly streamwater quality data combined with daily streamflow for six exurban and suburban watersheds in southeastern Pennsylvania to examine the relations among Ca2+, Mg2+, K+, Na+, chloride (Cl-), sulfate (SO42-), and alkalinity (HCO3-) concentrations and upstream controlling factors. Flow-normalized annual and baseflow (August ̶ November) concentrations for Ca2+, Mg2+, Na+, and Cl- increased in all six watersheds over the 20-year study, providing evidence of FSS’s impacts to groundwater that sustains streamflow. Additionally, a redundancy analysis using 2019 flow-normalized values identified the following positive associations between solute concentrations and controlling variables: 1) Cl-, Mg2+, and Ca2+ with impervious surface cover (ISC), 2) Na+ and SO42- with ISC and total WWTP discharge volume, and 3) HCO3- with agriculture and total WWTP discharge volume. From a human health perspective, 2019 flow-normalized Na+ concentrations exceeded the U.S. Environmental Protection Agency’s 20 mg L-1 threshold for individuals restricted to a low sodium diet. Furthermore, indices used to evaluate the corrosivity of source waters to drinking water infrastructure and inform municipal water treatment practices, such as the Chloride to Sulfate Mass Ratio and Larson Ratio, substantially increased over the 20-year time. Collectively, the results elucidate the causal factors of the FSS in suburban and exurban watersheds and its potential impacts to human health and drinking water infrastructure.